A Project Report on Congestion Control and Fairness in Wireless - ABHISHEK SHARMA, NISHANT AGRAWAL, and SARAVANAN K P (2010)
INNTERNAL Guide : Sharavana K. EXTERNAL Guide: Jyotishi B K USN No : 1MJ007CS002, 1MJ07CS052 and 1MJ06CS043 Carried out at : Mvj College Of Engineering Bangalore Acc No : PR1739
Keywords: Control and Fairness in Wireless